2018
DOI: 10.1161/strokeaha.118.020747
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Reduces tPA (Tissue-Type Plasminogen Activator)-Induced Hemorrhage and Microvascular Thrombosis After Embolic Stroke in Rat

Abstract: Many neuroprotective agents, some promising, have been tested as adjunctive therapy with tPA to reduce its Background and Purpose-Taurine (2-aminoethansulfolic amino acid) exerts neuroprotective actions in experimental stroke. Here, we investigated the effect of taurine in combination with delayed tPA (tissue-type plasminogen activator) on embolic stroke. Methods-Rats subjected to embolic middle cerebral artery occlusion were treated with taurine (50 mg/kg) at 4 hours in combination with tPA (10 mg/kg) at 6 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 51 publications
1
36
0
1
Order By: Relevance
“…And rt-PA also mediates neuronal destruction through plasmin proteolysis (Tsirka et al, 1995;Tsirka et al, 1996). Delayed rt-PA can also cause secondary thrombus formation in downstream microvessels (Jin et al, 2018). Consistent with this literature, we found that 2-BFI + rt-PA (8 h) was unable to rescue BBB integrity in our study, as the negative effects of rt-PA treatment at 8 h blocked the majority of the beneficial effects of 2-BFI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…And rt-PA also mediates neuronal destruction through plasmin proteolysis (Tsirka et al, 1995;Tsirka et al, 1996). Delayed rt-PA can also cause secondary thrombus formation in downstream microvessels (Jin et al, 2018). Consistent with this literature, we found that 2-BFI + rt-PA (8 h) was unable to rescue BBB integrity in our study, as the negative effects of rt-PA treatment at 8 h blocked the majority of the beneficial effects of 2-BFI.…”
Section: Discussionsupporting
confidence: 87%
“…LOX inhibitor LOXBlock-1 have all shown promise as adjuvant therapies that can be combined with rt-PA (Zhang et al, 2009;Chen et al, 2017;Jin et al, 2018). An effective postischemic neuroprotective agent would permit the benefits of rt-PA and block all the negative effects, including reduced rt-PA neurotoxicity, reduced risk of hemorrhage, decreased reperfusion injury, amplified neuroprotective effect and increased therapeutic time window.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, taurine showed a considerable decrease in UIA patients compared with controls. Taurine has been shown to reduce inflammatory injury in various diseases and to play a protective role in acute ischemic stroke 29 , traumatic brain injury 30 , subarachnoid hemorrhage 31 , and aortic aneurysm formation 32 . Depletion of the taurine transport system has been reported in the microbiome in atherosclerotic cardiovascular disease 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously hypertensive rats (SHRs, male, 12–15 week-old, weighing 270–310g, from Charles River Laboratories) were subjected to embolic middle cerebral artery occlusion (MCAO) according to the standard operating procedure in our laboratory [18, 21].…”
Section: Methodsmentioning
confidence: 99%